Studies on the background of cowpea seeds from trained community based and licensed seed producers in three states of Nigeria - Iyorkaa, N.; Kamara, A.; Omoigui, L.; Odo, P.E.; Teryima, I.; Ekeuro, G.C. (2021)
The survey was carried out to compare two main sources of cowpea seed, Community Based Seed Producers (CBSP) and Licensed Seed Producers (LSP) for their source of seeds, seed production and storage systems across the three states of Benue, Kano, and Jigawa. Seed producers were interviewed during seed collection using multiple-choice questions that were divided into three main categories to enable the researcher to get information on the following parameters; background of the seed or planting material of the seed producers, seed production and Seed storage background. Questionnaires were administered to Ninety (90) respondents each from both community based seed producers (CBSP) and licensed seed producers (LSP) across the three states to give a total of 180 respondents with the help of extension agents who were trained by the researcher in order to ensure consistency in response of the questions from the respondents. Copies of the questionnaires administered to the respondents were collected immediately from respondents after completion. Data collected from seed producers interview was presented in percentages using bar charts, histogram, line graphs, pyramids and radar webs using Minitab, version 2017 statistical software. The result showed that most of the community-based seed producers adapt to the technology introduced to them by the Tropical Legume III project. Community based seed producers are comparable with the licensed seed producers in most of the seed production practices and post-harvest handling. Community based seed producers are comparable with the licensed seed producers in most of the seed production practices and post-harvest handling. Most of the community based seed producers also adapt to the technology introduced to them by the TLIII project. We therefore, concluded that community based seed producers can be used as an alternative source for seed multiplication and distribution within their environs under good training and minimum inspection as there are comparable to the licensed seed producers in most seed production and postharvest handling.